UJI AKTIVITAS ANTIBAKTERI DARI ESTRAK TUMBUHAN AKWAY (Drimys beccariana. Gibbs) - Apriani S. Parubak (Jurnal Natural, 2010)
The plant Akway (Drimys beccariana.Gibbs) is endemic to Papua and is frequently used traditionally by the Arfak tribe as a medicinal plant. We extract the plant by maceration with ethanol. The antibacterial test is done by Agar diffusion method. As microba test we used Escheresia coli and Bacillus subtilis. Result obtained from fitochemistry skrinning of the leaf and bark contained alkaloid, flavonoid, steroid, tannin, glikosida, saponin, triterpenoid, steroid and fenolik. Concentration of active substances from the leaf are flavonoid (0,3680%) and tanin (10.33 %); while from the bark flavonoid 18.35% and tanin (27.65%). Antibacterial test showed that the plant could be used as an antibaterial substances. The test showed a moderate up to a strong blocking against Escherecia coli (a gram negative bacteri) and Bacillus subtilis (a gram positive bacteri). Thus it could be concluded that the Akway plant contain a substance with a bacteriostatic nature that could block the activity of the bacteri.